BANTUAN BAGI KELUARGA NELAYAN TRADISIONAL PADA MASA PANDEMI COVID-19 DI DESA KUALA SECAPAH MEMPAWAH HILIR KABUPATEN MEMPAWAH (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Abstract The problems experienced by the traditional fishermen of Kuala Secapah Village during the COVID-19 Pandemic: (a) In developing their business, including; the problem is that the capital they have is very limited, the means of catching sail boats and fishing gear are very simple, (b) the natural challenges when going to sea include; weather conditions are uncertain so that operations are relatively close, and dependence on wind direction is very high, (c) marketing of the catch includes; fish quality is low, the habit of borrowing money from a placeholder (tauke), facilities for marketing fish catches are not yet supported. The Community Service Team of FISIP Tanjungpura University in collaboration with the Kuala Secapah Village Government located at the Village Hall conducted outreach activities about the business of making cakes to be marketed to the public. Active involvement in marketing fish from the business results of her husband/parents directly to the community; (2) motivating fishermen's families not to be consumptive; (3) provide cash assistance in the amount of Rp. 150,000,- to 50 (fifty) heads of families (KK), with priority to: (a) heads of traditional fishing families using fishing equipment to sails; (b) the wife of a traditional fisherman whose husband has died, and; (c) traditional fishermen whose living conditions are very poor. Keywords: Assistance, Traditional Fishermen, COVID-19 Pandemic